A Comparison of Preservation Management Strategies for Paper Collections. (2nd January 2021) - Duran-Casablancas, Cristina; Strlič, Matija; Beentjes, Gabriëlle; de Bruin, Gerrit; van der Burg, Jaap; Grau-Bové, Josep
ABSTRACT: This paper proposes the use of simulation modelling to explore the effect of conservation strategies on the preservation of paper collections. Agent-based simulation was chosen as the simulation approach in order to capture the individual characteristics of the collections, their size, and the values of pH and degree of polymerisation (DP) for individual items. This approach enabled the simulation of the chemical degradation of different types of collections during their lifetime and under different preservation scenarios. We conducted a series of computational experiments on three types of collections, acidic, modern, and mixed, to explore the effect of slightly lowering the temperature and relative humidity in the repositories, the deacidification of part of the collection at different rates, and the delay in making the decision to start a deacidification treatment. The results indicated that a small change, lowering the storage conditions from 18°C to 16°C and from 50% to 40% RH, can protect up to 30% of the collection from reaching the critical DP of 300 within a time horizon of 500 years. On the other hand, to obtain similar results through deacidification, 45% of the mixed collection and 70% of the acidic collection should be deacidified within a period of 100 years. The experiments also indicated that better results are obtained when the priorities for deacidification are acidic records with a pH value below 5. This study shows that modelling the heterogeneity of the collections can support preservation management, particularly if the concern is not the preservation of a part of the collection but the collection as a whole.